PEMBERDAYAAN UMKM MELALUI OPTIMALISASI KETERAMPILAN KREASI KONTEN MEDIA SOSIAL UNTUK MENINGKATKAN PENJUALAN DI DESA PEKIK NYARING KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Arma Putra; Apri Andani; Ketut Sukiyono; Indra Cahyadinata; Melli Suryanty (UNIB Press, 2026)
This community service program aims to improve the skills of MSMEs in Pekik Nyaring Village, Pondok Kelapa District, Central Bengkulu, in creating social media content as a digital marketing strategy. This village, which has potential for processed agricultural products such as elephant ear chips, banana chips, rengginang (rice crackers), and various cassava products, still faces limitations in utilizing social media as a promotional tool. Activities were carried out through observation, digital content management counseling, content planning and creation training, and digital administration. The training emphasized hands-on practice in product photography, lighting, visual composition, image editing using mobile apps, as well as creating captions, hashtags, and content calendars. Results showed significant improvements in participants' ability to produce upload-ready content and understand basic digital marketing strategies. Despite obstacles such as varying device quality, limited internet access, and limited technical skills, the adaptive approach ensured that all participants were able to optimally follow the process. This program has had a positive impact on improving MSMEs' readiness to independently promote their products on social media. Moving forward, advanced graphic design-based training is crucial so participants can create more engaging, professional, and uniform content templates and frameworks to enhance product competitiveness.